Perbaikan Kinerja Defect free supply chain Dengan Pendekatan Simulasi Model System Dynamics (Studi Kasus: PT. NPC) - Mansur, Agus; Rifki, Muhammad; Ramadhan, Fadhil Adita Ramadhan (Jurnal Rekayasa Industri (JRI), 2025)
The garment industry plays an important role in supporting the Indonesian economy with a significant growth of 15.08% in 2019. This study aims to reduce the defect rate at Line 9 Factory C, PT. NPC to strengthen supply chain performance, especially performance related to the defect free supply chain. This study will explore in detail the production defect rate using the Seven Tools approach and design a defect reduction strategy with a Dynamic System Simulation approach. The Seven Tools method helps identify dominant defects such as Poor Shape, Open Seam, and Broken Stitch through Check Sheet, Pareto, and Fishbone Diagram analysis. The simulation results show that the Company's existing condition has an average defect rate of 12.15%, exceeding the company's target of less than 10%. The proposed strategic steps are to conduct interventions in the form of intensive training for operators and the addition of Inline QC officers. The simulation results show that training reduces the defect rate by 0.70%, while the addition of Inline QC officers reduces the defect rate by 1.16%. The combination of both strategies resulted in the largest reduction in defect rates of up to 1.34%, indicating a positive direction of improvement towards the company's target. The implementation of quality control strategies not only increased operational efficiency, but also increased the company's supply chain performance.